Penerapan Algoritma K-Means Clustering Data Penduduk Miskin Berdasarkan Desa di Kecamatan Tana Righu - Arinto Umbu Dasa; Gergorius Kopong Pati; Emirensiana Dappa Ege (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Expert systems are one type of computer technology that is being used by a used in the medical field to assist physicians in patient examinations is expert systems.The goal of this is to improve patient care both now and in the future.system with expertise is an application that replicates how an expert would reason to solve a particular problem or acts similarly to an expert due to its understanding of a knowledge base that has to be processed and its ability to solve problems. An expert system's diagnosis of epilepsy leads to the creation of a system that can offer individuals with the condition a consultation service for the purpose of diagnosing the condition and providing information on treatment options. This is demonstrated by the development of numerous technologies that facilitate the work of numerous parties. One of them is computer-related and uses Expert System Science to assist in the diagnosis of epilepsy. The Certainty Factor approach is employed in this study. Thirteen symptoms and three different forms of epilepsy—general, partial, and secondary—were used in this investigation. The study's findings indicate that, based on the chosen symptoms, the most accurate diagnosis is Partial Primary, Partial Secondary, with a confidence level of 74%, and the most accurate diagnosis is Generalized Epilepsy, with a confidence level of 99%.